KAJIAN PSIKOLOGI BELAJAR: MENGUKIR PRESTASI MELALUI PENGENALAN DIRI DAN OPTIMALISASI POTENSI - Eny Purwandari (Universitas Muhammadiyah Surakarta, 2007)
Self knowledge is a process which must be conceded by everyindividual. In this process, it is likely that an individual knows his strengthand weakness. The strength does not always cause benefit, on the otherhand the weakness does not always cause a misplace. However, if bothof them are managed well, it will cause something extraordinary. Thestudent has to know his self knowledge to get the best achievement. Someof the things that should be considered are: style of learning, emotionand the ways of life orientation. For the students of MAN I Sragen, thelearning style tends to be auditory. They manage their emotion well enough,and their ways of life are focused on three things namely: spirit, familyharmony, and achievement. Based on the result of social service, thestudents and the teachers have to use and maximize it well so that theirpositive potential can be optimized and developed well either individuallyor collectively in the educational institution.